1987
DOI: 10.1164/ajrccm/136.3.730
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Volume Curve of Total Respiratory System in Acute Respiratory Failure: Computed Tomographic Scan Study

Abstract: To investigate the relationship between lung anatomy and pulmonary mechanics in acute respiratory failure (ARF), 20 patients with ARF underwent computerized tomography (CT) at 3 levels of positive end-expiratory pressure (PEEP) (5, 10, and 15 cm H2O). The static pressure-volume curve of the total respiratory system and the lung volumes (helium dilution method) were also measured. By knowing the lung volumes and analyzing the CT number frequency distribution, a quantitative estimate of normally aerated, poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
427
2
45

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 802 publications
(487 citation statements)
references
References 6 publications
13
427
2
45
Order By: Relevance
“…However, several studies have shown evidence of recruitment beyond LIP (21,23,27). The concept of ongoing recruitment throughout lung inflation has also been supported by mathematical models (12), human studies utilizing computer tomography of the chest (8), and animal models (33). Thus controversy already exists over how recruitment is best served by PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown evidence of recruitment beyond LIP (21,23,27). The concept of ongoing recruitment throughout lung inflation has also been supported by mathematical models (12), human studies utilizing computer tomography of the chest (8), and animal models (33). Thus controversy already exists over how recruitment is best served by PEEP.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the pathological findings of PCP in AIDS patients include interstitial infiltrates associated with alveolar occupation by eosinophilic exudates, hyaline membranes, macrophages, and cellular debris, which oppose recruitment, whilst oedema is moderate or absent [8,9]. Moreover, computed tomography scan performed in eight of our patients exhibited homogeneous diffuse interstitial and alveolar infiltration, at variance with what appears to be the most common finding in ARDS patients in whom dense opacities are mainly confined to the dependent lung regions [27]. Because the presence of an inflection point is taken to indicate alveolar recruitment, the present findings suggest that in AIDS patients with ARDS and PCP there is no substantial alveolar recruitment during lung inflation.…”
Section: Static Inflation V-p Curvementioning
confidence: 50%
“…1 and 2). According to some authors [25][26][27], in ARDS patients without AIDS and PCP the inflection point is a common occurrence, though this might not be particularly frequent according to other studies [22,[28][29][30]. It has been suggested that the inflection is present in the earliest stage of ARDS, whereas later on, probably as a result of oedema resolution, the inflection disappears with or without increases or decreases in elastance, probably depending on the pattern of fibrosis development [26].…”
Section: Static Inflation V-p Curvementioning
confidence: 99%
“…To eliminate the CO 2 , the lungs must be ventilated. As in ARDS, the "baby lung" [4,5] may be extremely small, and each tidal volume entering the baby lung will dilute the CO 2 to a far greater extent than with a normal FRC. The expired end-tidal CO 2 will be proportionally lower and measured as increased alveolar dead space.…”
mentioning
confidence: 99%